New institutional investors in the IPO secondary market: Sentiment or fundamentals?. (10th June 2021) - Fu, Xudong; Hamilton, Janet; Lian, Qin; Tang, Tian; Wang, Qiming
Abstract: We investigate new institutional investors that do not receive initial public offering (IPO) allocations but invest in the newly public firms after IPOs. We find that many institutions buy the stocks of IPO firms in the post‐IPO secondary market over time. In contrast to retail investors who chase hot IPOs, these new institutions invest in IPO firms with lower valuations at offerings and better fundamentals. These results suggest that new institutional investors' post‐IPO investment decisions are driven by publicly available information on firm fundamentals instead of investor sentiment. Long‐term performance tests confirm that this trading strategy helps institutions identify better quality IPOs.